Influence of linear and branched amine functionalization in mesoporous silica on the thermal, mechanical and barrier properties of sustainable poly(lactic acid) biocomposite films. (18th July 2018) - Loganathan, Sravanthi; Jacob, Jissy; Valapa, Ravi Babu; Thomas, Sabu
Abstract: Recently, biopolymer based materials are regarded as potential alternative for conventional plastics. Poly (lactic acid) (PLA) is one among the biopolymers, which is rapidly commercialized for food packaging application. However, PLA has its own limitations, which confines its commercial application in food packaging sector. With the aim to overcome these limitations, an effort has been undertaken in the current work to use organically modified pore expanded MCM-41 mesoporous silica (MS) as filler for fabrication of PLA based composites via solution casting method. The current work investigates the influence of incorporation of linear (tetraethylene pentamine & pentaethylene hexamine) and branched (polyethylenimine) amine impregnated MS on the morphological, structural, thermal, mechanical and barrier properties of PLA. The N2 adsorption-desorption isotherms, surface area and pore volume analyses clearly indicated that the mesopores present in MS are filled with amine moieties after modification using impregnation agents. Thermo-gravimetric analysis revealed that the branched amine impregnated MS showed enhanced T onset and T max values in comparison with neat PLA and PLA composites impregnated with linear (L1 and L2 ) amine. DSC results confirmed that the incorporated branched amine modified MS acted as nucleating agent by enhancing the crystallization rate for PLA. Mechanical studies revealed that the presence of branched amine in MS helped in enhancing the ductility property for PLA-MS composite films. Oxygen transmission rate analysis indicated that the presence of branched amine modified MS in the PLA matrix enhanced tortuosity path for passage of O2 molecules through the films. All these results indicated that the branched amine impregnated MS incorporated PLA composite film shows promising features for sustainable food packaging. Graphical abstract: Image 1 Highlights: Influence of various amine functionalized MS on the properties of PLA is investigated. High compatibility between PLA and branched amine functionalized MS (BAFMS) is achieved. BAFMS significantly improved the thermal, mechanical and barrier properties of PLA.